Organization of transcriptional signals in plasmids pBR322 and pACYC184. - Stüber, D (1981)
Electron microscopic analysis of in vitro transcriptional complexes of pBR322 and pACYC184 revealed five and six major transcriptional units, respectively, in these two plasmid vectors. These units are transcribed with various efficiencies, depending upon the individual promoter strengths, which differ in pBR322 up to 10-fold. A most interesting signal arrangement was found at the beginning of the tetracycline resistance region, where two partially overlapping promoters (P1 and P2) initiate transcription crosswise in opposite directions. Whereas P2 is known to promote tetracycline resistance and to be inactivated by HindIII cleavage, P1 is able to transcribe DNA integrated at that site and probably contributes to the expression of the beta-lactamase gene in pBR322. In pACYC184, besides P1, P2, and the cat (chloramphenicol resistance) promoter (P5), two initiation sites (P3 and P4) were mapped in a region that appears to be part of insertion sequence 1. The maps of transcription signals permit a more predictable utilization of these cloning vehicles and also allow the reinterpretation of earlier cloning results.